2023
DOI: 10.1186/s12951-023-01969-1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic bodies: bioactive treasure left behind by the dying cells with robust diagnostic and therapeutic application potentials

Abstract: Apoptosis, a form of programmed cell death, is essential for growth and tissue homeostasis. Apoptotic bodies (ApoBDs) are a form of extracellular vesicles (EVs) released by dying cells in the last stage of apoptosis and were previously regarded as debris of dead cells. Recent studies unraveled that ApoBDs are not cell debris but the bioactive treasure left behind by the dying cells with an important role in intercellular communications related to human health and various diseases. Defective clearance of ApoBDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 198 publications
0
10
0
Order By: Relevance
“…Another study reported that AC removal by macrophages limited the release of thromboxane-B2 ( 57 ). Gradually, researchers began to regard the apoptotic cargos as “bioactive treasures” released from dying cells, which promoted a pro-resolving macrophage phenotype ( 58 ). Efferocytosis enables anti-inflammatory and homeostatic maintenance.…”
Section: Physiological Functions Of Macrophages During Efferocytosismentioning
confidence: 99%
“…Another study reported that AC removal by macrophages limited the release of thromboxane-B2 ( 57 ). Gradually, researchers began to regard the apoptotic cargos as “bioactive treasures” released from dying cells, which promoted a pro-resolving macrophage phenotype ( 58 ). Efferocytosis enables anti-inflammatory and homeostatic maintenance.…”
Section: Physiological Functions Of Macrophages During Efferocytosismentioning
confidence: 99%
“…The biogenesis of apoptotic bodies starts with the initiation of cell apoptosis, which requires chromatin condensation, nuclear shattering, and cell shrinking, with the concomitant formation of blebs, which constitute the so-called microtubule spikes, as well as the apoptopodia. At the end of this procedure, the apoptotic vesicles are formed, after the segmentation of the apoptotic bodies [ 21 ].…”
Section: A Brief Analysis Of the Ev And Mirna Biogenesis Mechanismmentioning
confidence: 99%
“…On the other hand, ectosomes are vesicles ranging from 50 nm to 10000 nm that are directly shed from the plasma membrane of both healthy and damaged cells 8 . While apoptotic bodies, one of the most well-studied subtypes of ectosomes, are submicron vesicles only derived from cells undergoing programmed cell death 9 . Recently, membranous vesicles produced by migrating cells at the near ends are identified as a novel subtype of EVs and referred to as “migrasome”, whose roles in cellular communication are under extensive exploration 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%